ADOPTION OF MOBILE GOVERNMENT SERVICES USING AN EXTENDED UTAUT2 MODEL - Al-awj, Jalal; Mohd Danuri, Mohd Shahrul Nizam; Abdul Ghani, Norjihan; Ahmad, Syarbaini (Malaysian Journal of Computer Science, 2024)
The primary aim of this research is to formulate an extensive model for the adoption of mobile government (m-government) from the people's viewpoint. The research enhanced the Unified Theory of Acceptance and Use of Technology (UTAUT2) by incorporating various technological, political, and personal factors, including service diversity and quality, governmental trust, mobile internet, innovativeness, and self-efficacy. The proposed approach is subsequently evaluated using a comprehensive survey of 512 Yemeni citizens across two cities. The statistical research indicated that innovativeness was the most significant factor influencing citizens' intention to utilize m-government. The diversity and quality of services are the primary elements affecting citizens' utilization of m-government services. The PLS analysis indicates that the suggested model accounts for 58% of citizens' intention to utilize m-government services. Moreover, the proposed augmentation of UTAUT2 in this study significantly enhanced the variance elucidated for the baseline model. The implications of the discoveries are examined.